Analisis Faktor-Faktor Risiko Malaria Di Daerah Endemis Dengan Pendekatan Spasial Di Kabupaten Purworejo - Darundiati, Yusniar Hanani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACK Background: Malaria remains serious public health problem in Indonesia. More than half of the total population of Indonesia still live in area where are malaria transmission occurred. The biggest number of prevalence in Central Java occurred in Purworejo District, i.e. 15,156 cases in 2001. Malaria transmissions are influenced by several factors besides epidemiological factors : environmental factors, health services factors, the mobility of the population, socio-economic factors and behavior factors. Malaria control programme should estimates the environmental condition and involves several epidemiological components which have much contribution in malaria control programme. Methods : This study is an observational research using cross-sectional approach. The independent variables are outdoor and indoor environmental factors, behavior factors, health services factors, socio-economic factors and mobility of population. The dependent variable is malaria cases among family members. Samples concist of 168 respondents from two MCI villages and two HCI villages of Pituruh Sub district. Analysis were conducted by applying multiple logistic regression. Results : The bivariate analysis shows that there are significant associations between the environmental, behavior, health services factors and the malaria occurance among respondent’s family members. The multivariate analysis concludes that distance between respondents’ house and the breeding places more than 2 km (OR = 0.263; 95% CI = 0.102 – 0.676), the absence of cattles in respondents’ house (OR = 0.395; 95 % CI = 0.160 – 0.676) and the absence of kapulaga/salak plants (OR = 0.209; 95% CI = 0.098 – 0.446) are the protective factors of malaria occurance among respondent’s family members. Conclusions : Repondents who live in houses where the distance is more than 2 km away from the breeding places have risk 0.263 times less than those who live in houses where the distance is less than 2 km. Respondents who don’t have cattles and kapulaga/salak plants around their houses have risk 0.395 and 0.209 times less than those who have cattles and kapulaga/salak plants around their houses. Key words : Malaria, Risk Factors, Endemic Area, Spatial Approach